2009
DOI: 10.1121/1.3203209
|View full text |Cite
|
Sign up to set email alerts
|

The player and the bowed string: Coordination of bowing parameters in violin and viola performance

Abstract: An experiment was conducted with four violin and viola players, measuring their bowing performance using an optical motion capture system and sensors on the bow. The measurements allowed for a detailed analysis of the use and coordination of the main bowing parameters bow velocity, bow force, and bow-bridge distance. An analysis of bowing strategies in detache playing of notes of three durations (0.2, 2, and 4 s) at three dynamic levels (pp, mf, and f) on all four strings is presented, focusing on the "steady"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…4 show the averages of the bow-bridge distance (β) and bow velocity per player in scale2. Generally, both bowing controls increased due to higher tempo (160 bpm) which agrees with results reported in [3] and [4]. The observed absolute bow-bridge distance was 7.56 cm (0.49) on average, with the minimum and maximum values equal to 3.16 and 11.88 cm (β = 0.78 and 1.61) respectively (for the individual values per player see Table 1).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…4 show the averages of the bow-bridge distance (β) and bow velocity per player in scale2. Generally, both bowing controls increased due to higher tempo (160 bpm) which agrees with results reported in [3] and [4]. The observed absolute bow-bridge distance was 7.56 cm (0.49) on average, with the minimum and maximum values equal to 3.16 and 11.88 cm (β = 0.78 and 1.61) respectively (for the individual values per player see Table 1).…”
Section: Resultssupporting
confidence: 79%
“…For a comparative analysis of the players the bowing control parameters and audio features were calculated on the sustained parts of notes, excluding first 200 ms of the transition and attack portions in scale1 and 100 ms in scale2 respectively [4]. To summarise sequences of the parameters independently from the varying lengths of notes, mean and standard deviation values across notes were first calculated (median values for audio features) and subsequently averaged across strings and cellos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal bow force would produce pitching torque to rotate the neck of the violin downward around the shoulder rest, and drawing force would produce torque to rotate the violin medially or laterally (rolling movement) on the shoulder. Askenfelt and Jansson (1992) reported that the bow's pressing force was around 0.5 N at p, which increased to 2 N at f (Askenfelt and Jansson 1992) and 4 N in extreme cases (Schoonderwaldt 2009). Askenfelt and Jansson also stated that the drawing force when the bow was in motion would be relatively small (0.1-0.2 N), but it might reach 2 N when Fig.…”
Section: Chin Force During Violin Performancementioning
confidence: 96%
“…This is done using empirical data from ap erformance study with advanced violin and viola players [27], whose bowing actions were recorded using am ethod developed by Schoonderwaldt and Demoucron [16]. This method allows for an accurate measurement of all three bowangles.…”
Section: Aims Of the Studymentioning
confidence: 99%